An efficient and cost-effective protocol for selecting transcription factor binding sites that reduces isotope usage. - Krystel, J.; Ayyanathan, K. (Journal of biomolecular techniques : JBT, 2012)
To function, transcription factors must position themselves by binding to DNA in a sequence-specific manner. Knowing the binding sites of these factors is a necessary step in understanding their activity. The standard protocols used for selecting a consensus-binding sequence for a DNA binding domain often require the use of radioisotopes to attain the necessary level of power in the assay. Alternatives are often less sensitive and may require an expensive apparatus for visualizing. We have created a modified binding site selection (BSS) protocol to improve efficiency and decrease the use of radioisotope. A GST affinity-tagged DNA binding domain construct was immobilized on a GSH affinity column and used to select from a randomized oligonucleotide library identical to those typically used in a radiolabeled BSS protocol. This produced a library specifically pre-enriched for use in a standard sequential EMSA selection. Use of a pre-enriched library reduced the total number of labeled rounds required for selection, decreasing the use of radioisotope while maintaining efficacy. The protocol was used to select for the binding sequence for several Drosophila melanogaster transcription factors. The consensus sequence was then shown by competitive binding experiments to associate with the protein in a sequence-dependent manner.